RENAL OSTEODYSTROPHY IN PATIENTS WITH END-STAGE RENAL INSUFFICIENCY RECEIVING HEMODIALYSIS AND WAYS OF ITS CORRECTION (Conferencea, 2022)
The aim of the study is to optimize the early diagnosis of demineralization of the skeletal system and the treatment of osteoporosis in patients receiving program hemodialysis at the fifth stage of chronic kidney disease.